Sosial Media Effect terhadap Mental Health Adolescent di Tengah Transformasi Digital: Studi Komprehensif tentang Psikologis dan Risiko Terkait - Genta Rizki Alfaridzi; Elisabet Mediana Putri; Sulistiasih Sulistiasih (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This paper examined the role of social media on mental health amidst the acceleration of digital transformation. The increasing engagement of young people in social media platforms has raised major concerns regarding its impact on psychological well-being. This study investigates that there is a strong correspondence of social media consumption and the emergence of mental health issues such as depression and anxiety and social isolation among adolescents. Data shows a significant increase in screen/mobile time among Indonesian adolescents, with average daily use exceeding global recommendations and correlating with high incidence of mental health disorders. This study utilized a comprehensive review of the existing literature, as well as engaging multiple academic sources to assess the cumulative impact of the digital Effect. Key findings suggest that excessive interaction with digital platforms potentially increases risk of cyberbullying, body image problems, depression, anxiety, self-harm, suicidal tendencies and substance consumption. Another finding, that exposure to sexual content or pornographic sites on the internet, is a predictor of increased sexual activity and premarital sex. This is an important concern, highlighting the adverse impact of prolonged digital effects on adolescents' mental resilience and life satisfaction. This research underscores the urgent need for strategic interventions and policy frameworks to mitigate the negative effects of social media on mental health holistically.